Performance measure of online system acceptance and customer satisfaction through airlines websites in Malaysia - Khan, H. (Inderscience Enterprises Ltd., 2017)
Online system and websites are the new emerging channels by the companies to attract the customers around the globe. The online system provides the valuable information about the company's product and services. Customers can acquire all information from the company's website. This paper aims to measure the customer satisfaction with airline websites along with customer acceptance of online system. This means to be a new research area for the information system acceptance researcher. Data was collected from 130 respondents who use airline website for making their travel related decision. A survey approach was used to gather data by administering the questionnaire to the target customers. Statistical tests including correlation, regression and exploratory factor analysis are applied to test on data resulted in support of all hypothesis. The result indicates that all independent variables have strong significant impact on customer satisfaction with online system acceptance and with customer satisfaction. Copyright © 2017 Inderscience Enterprises Ltd.